2018
DOI: 10.1002/term.2705
|View full text |Cite
|
Sign up to set email alerts
|

Repair potential of nonsurgically delivered induced pluripotent stem cell-derived chondrocytes in a rat osteochondral defect model

Abstract: Human induced pluripotent stem cells (hiPSCs) are thought to be an alternative cell source for future regenerative medicine. hiPSCs may allow unlimited production of cell types that have low turnover rates and are difficult to obtain such as autologous chondrocytes. In this study, we generated hiPSC-derived chondrogenic pellets, and chondrocytes were isolated. To confirm the curative effects, chondrogenic pellets and isolated chondrocytes were transplanted into rat joints with osteochondral defects. Isolated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…Repairing of articular cartilage lesion remains a challenging issue because of its avascular and aneural nature [ 26 ]. All reparative approaches were trying but failed to achieve the ultimate goal of regeneration and restoration of the hyaline cartilage in the defected area [ 27 ]. Cartilage-to-cartilage integration is extremely difficult to achieve because cartilage displays low metabolism and contains dense, antiadhesive ECM [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Repairing of articular cartilage lesion remains a challenging issue because of its avascular and aneural nature [ 26 ]. All reparative approaches were trying but failed to achieve the ultimate goal of regeneration and restoration of the hyaline cartilage in the defected area [ 27 ]. Cartilage-to-cartilage integration is extremely difficult to achieve because cartilage displays low metabolism and contains dense, antiadhesive ECM [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the successful cartilage formation from iPSC-derived teratoma tissue, this method is not suitable for replacement therapies for OA patients due to transplant animal growth as well as the time-and cost-consuming differentiation process [23]. Recently, the research group of Rim et al [24] proved the therapeutic effect of iPSC-derived chondrocytes delivered only by single intra-articular injection into the rat model with the osteochondral defect. Eight weeks post-transplantation, the high recovery capacity of injected iPSC-derived chondrocytes, which formed lacunae in vivo, were detected.…”
Section: Induced Pluripotent Stem Cell (Ipsc)-based Osteoarthritis Momentioning
confidence: 99%
“…A short time ago, it was found that the paracrine factors such as Ihh and Runx also influence chondrogenic differentiation of iPSCs [28][29][30]. There are currently four main chondrogenic differentiation approaches including (a) the generation of MSC-like iPSCs and their subsequent differentiation into chondrocytes [31,32]; (b) the co-culture of iPSCs-derived MSCs with primary chondrocytes [33]; (c) through the formation of embryoid bodies (EBs) [19,24,34,35]; and (d) culturing of iPSCs in a series of media architected to mimic normal developmental pathways [20,22]. iPSC formation through EBs together with their subsequent co-cultivation with chondrocytes was performed by Wei et al [35].…”
Section: Differentiation Of Ipscs Into Chondrocytesmentioning
confidence: 99%
“…Chondrogenic differentiation was conducted using our previous methods [5,[9][10][11][12]. A 1:1 mixture of E8 media (Thermo Fisher Scientific) and Aggrewell media (StemCell Technologies, Vancouver, BC, Canada) was added to hiPSCs (1-5 × 10 4 cells per cm 2 ) for embryonic body (EB) formation, which were maintained in a petri dish with E8 media and 10 µM rho-associated kinase (ROCK) inhibitor (ROCKi) for 24 h. The formed EB clusters were then maintained in E8 media without ROCKi for an additional 48 h.…”
Section: Chondrogenic Differentiation Using Pellet Culturementioning
confidence: 99%